SDGs Policy Analysis: Strategy Towards Sustainable Cities and Poverty Alleviation in Mojokerto Regency: Analisis Kebijakan SDGs: Strategi Menuju Kota Berkelanjutan Dan Pengentasan Kemiskinan Di Kabupaten Mojokerto - Taufiq, Eddy (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
This study analyzes the implementation of Sustainable Development Goals (SDGs) policies, especially the goal of zero poverty and hunger, in sustainable development in Mojokerto Regency. The method used is a qualitative approach through literature studies, by reviewing various written sources such as scientific articles, government reports, and policy documents. The results of the study indicate that the integration of SDGs in regional development planning has driven a decrease in poverty rates in Mojokerto, reflected in the decreasing trend in the percentage of poor people over the past five years. Innovative programs such as Kampung Zakat and MSME assistance have contributed significantly to improving community welfare. However, the implementation of SDGs still faces challenges in the form of budget constraints, low community participation, and lack of cross-sector synergy. Progress in poverty and hunger alleviation, the sustainability of achieving SDGs in Mojokerto requires strengthening collaboration, increasing human resource capacity, and optimizing funding.